Self-Efficacy to Obtain Human Papillomavirus Vaccination among Indonesian Adolescent Girls - Lismidiati, Wiwin (Asian Pacific Organization for Cancer Prevention, 2022)
Objective: This study aimed to examine self-efficacy to obtain the HPV vaccination among adolescent girls in Indonesia. Furthermore, factors affecting HPV vaccination self-efficacy was investigated. Methods: A cross-sectional study was conducted 337 among adolescent girls in junior high school (aged 12-15 years). Participants were recruited from four junior high schools in Yogyakarta using consecutive sampling. A self-administered questionnaire requested demographic information, knowledge of HPV and HPV vaccine and self-efficacy to obtain HPV vaccine. School teachers facilitate the data collection adolescent girls using the listed questionnaires. Data analysis used Pearson correlation, chi-squared tests and logistic regression analysis. Results: As many as 50.1% of the adolescent girls reported high self-efficacy to obtain HPV vaccine and 57.9% reported high knowledge about HPV and HPV vaccine. There were significant correlations between self-efficacy and age, vaccination experience, recommendation from health care providers, parental support, social persuasion and anxiety. Parental support contributed to almost 18 times (95% CI:3.837 - 83.648; p<0.0001) while social persuasion was nearly 9 times (95% CI: 3.875-20.011; p<0.0001) more likely to predict the self-efficacy to obtain HPV vaccination. Conclusion: Parental support and social persuasion significantly predict self-efficacy to obtain HPV vaccination. Parental support is the main factor in the decision making of adolescent to obtain HPV vaccination.